Information Systems, Technology and Management Third International Conference, ICISTM 2009, Ghaziabad, India, March 12-13, 2009. Proceedings - Prasad, Sushil K.; Routray, Susmi; Khurana, Reema; Sahni, Sartaj; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This book constitutes the refereed proceedings of the Third International Conference on Information Systems, Technology and Management, ICISTM 2009, held in Ghaziabad, India, in March 2009 The 30 revised full papers presented together with 4 keynote papers were carefully reviewed and selected from 79 submissions. The papers are organized in topical sections on storage and retrieval systems; data mining and classification; managing digital goods and services; scheduling and distributed systems; advances in software engineering; case studies in information management; algorithms and workflows; authentication and detection systems; recommendation and negotiation; secure and multimedia systems; as well as 14 extended poster abstracts.
Keynotes -- Embedded Sensor Networks -- Future of Software Engineering -- Seeing beyond Computer Science and Software Engineering -- System on Mobile Devices Middleware: Thinking beyond Basic Phones and PDAs -- Session 1. Storage and Retrieval Systems -- A Reduced Lattice Greedy Algorithm for Selecting Materialized Views -- Improving Expression Power in Modeling OLAP Hierarchies -- A Hybrid Information Retrieval System for Medical Field Using MeSH Ontology -- Session 2. Data Mining and Classification -- Mining Rare Events Data for Assessing Customer Attrition Risk -- Extraction and Classification of Emotions for Business Research -- Data Shrinking Based Feature Ranking for Protein Classification -- Session 3. Managing Digital Goods and Services -- Value-Based Risk Management for Web Information Goods -- Quality and Business Offer Driven Selection of Web Services for Compositions -- Managing Sustainability with the Support of Business Intelligence Methods and Tools -- Session 4. Scheduling and Distributed Systems -- A Novel Particle Swarm Optimization Approach for Grid Job Scheduling -- Priority-Based Job Scheduling in Distributed Systems -- An Efficient Search to Improve Neighbour Selection Mechanism in P2P Network -- Session 5. Advances in Software Engineering -- Application of Neural Networks in Software Engineering: A Review -- Model-Based Software Regression Testing for Software Components -- An Approach towards Software Quality Assessment -- Session 6. Case Studies in Information Management -- A Study of the Antecedents and Consequences of Members$1 (BHelping Behaviors in Online Community -- Mobile Forensics: An Introduction from Indian Law Enforcement Perspective -- A Study to Identify the Critical Success Factors for ERP Implementation in an Indian SME: A Case Based Approach -- Session 7. Algorithms and Workflows -- Hardware-Software Co-design of QRD-RLS Algorithm with Microblaze Soft Core Processor -- Classification of Palmprint Using Principal Line -- Workflow Modeling Using Stochastic Activity Networks -- Session 8. Authentication and Detection Systems -- AIDSLK: An Anomaly Based Intrusion Detection System in Linux Kernel -- New Quantization Technique in Semi-fragile Digital Watermarking for Image Authentication -- A Taxonomy of Frauds and Fraud Detection Techniques -- Session 9. Recommendation and Negotiation -- A Hybrid Approach for Knowledge-Based Product Recommendation -- An Integrated Rule-Based and Case-Based Reasoning Approach for Selection of the Software Packages -- Learning Agents in Automated Negotiations -- Session 10. Secure and Multimedia Systems -- On Performance of Linear Multiuser Detectors for Wireless Multimedia Applications -- A Trust Based Clustering Framework for Securing Ad Hoc Networks -- Security Enhancement in Data Encryption Standard -- Extended Abstracts of Posters -- A Novel Framework for Executing Untrusted Programs -- Comparative Analysis of Decision Trees with Logistic Regression in Predicting Fault-Prone Classes -- Software Security Factors in Design Phase -- Mathematical Modelling of SRIRE Approach to Develop Search Engine Friendly Website -- Personalized Semantic Peer Selection in Peer-to-Peer Networks -- An Ant Colony Optimization Approach to Test Sequence Generation for Control Flow Based Software Testing -- Component Prioritization Schema for Achieving Maximum Time and Cost Benefits from Software Testing -- Optimization of Software Testing Using Genetic Algorithm -- Study and Analysis of Software Development and User Satisfaction Level -- Influence of Hot Spots in CDMA Macro Cellular Systems -- An Overview of a Hybrid Fraud Scoring and Spike Detection Technique for Fraud Detection in Streaming Data -- PCNN Based Hybrid Approach for Suppression of High Density of Impulsive Noise -- An Overview of a New Multi-formalism Modeling Framework -- Association Rule Based Feature Extraction for Character Recognition.s
Keywords: Computer science; Software engineering; Data encryption (Computer science).; Data mining; Multimedia information systems; Management information systems; Computer engineering; Computer Science; Computer Engineering; Software Engineering/Programming and Operating Systems; Data Encryption; Management of Computing and Information Systems; Multimedia Information Systems; Data Mining and Knowledge Discovery; Electronic books